The first record of an association between a pontoniine shrimp (Crustacea: Decapoda: Palaemonidae: Pontoniinae) and a thalassematid spoon worm (Echiura: Thalassematidae), with the description of a new shrimp species - Marin, Ivan (Zootaxa, 2014)
A new pontoniine shrimp species, Eupontonia nudirostris sp. nov. (Crustacea: Decapoda: Palaemonidae: Pontoniinae), was found in association with the thalassematid spoon worm Listriolobus sp. (Echiura: Thalassematidae) in the mangrove littoral of Dam Bay of Tre Island, Nhatrang Bay, Vietnam. This is the first record of an association between symbiotic pontoniine shrimp and spoon worm as their host. The new shrimp species clearly differs from other representatives of the genus Eupontonia Bruce, 1971 by the unarmed rostrum with a blunt tip and the reduced antennal tooth on the carapace, which can be considered as an adaptation to symbiotic lifestyle inside cramped burrows of the host. A revised key to the genus Eupontonia Bruce, 1971 is presented.